The port of Belfast - Sinclair, Kenneth (Statistical and Social Inquiry Society of Ireland, 1957)
I have been asked to make the subject of my talk this evening the Port of Belfast. Many visitors to the Port, on being shown around, are surprised at its magnitude, and exclaim that previously they had no conception of the extent of its trade and the importance of the Undertaking. Now, although there are at least two publications extant giving many details about the growth of the Port?one published in 1917 by a former General Manager, Sir David Owen, and the other a brochure issued on the occasion of the Centenary of the Belfast Harbour Commissioners m 1947?I have a suspicion that many local people are also unaware that one of the world's major ports lies at their doorstep. I am, therefore, glad to be here and to have the opportunity of giving this talk to your Society.
Read before the Society, 2 November 1956
Keywords: Shipping; Trade; Port of Belfast; 314.15